Competition and Predation in Soil Fungivorous Microarthropods Using Stable Isotope Ratio Mass Spectrometry - Crotty, Felicity V.; Adl, Sina M. (Frontiers in Microbiology, 2019)
The soil food web is often described as having three main energy channels: root, bacterial and fungal. Here we provide quantitative data using a sensitive stable isotope ratio mass spectrometry procedure with microcosms on species interactions in the fungal pathway. We measured 15N and 13C enrichment in microarthropods through grazing rare isotope enriched fungal mycelia. Experimental treatments were various combinations of 1, 2, 3, 4 microarthropods species. We used three fungivores (the collembolan Lepidocyrtus curvicollis, the Astigmata Tyrophagus putrescentiae, the Oribatida Oribatula tibialis.), and the Mesostigmata predator Hypoaspis acquilifer We collected individuals of each species separately, as well as their faeces, and moult where available. All three fungivorous microarthropods consumed significantly more than their own body weight per day. The three fungivores differed in their consumption of the mycelium as it was not equally palatable to each. The Mesostigmata predator Hypoaspis also differed in its microarthropod prey preference. In multiple species combinations microarthropod behavioural interactions modified consumption and predation rates. Our selection of mites of different sizes, with varied preference for the mycelium, combined with differing predation rates on each mite, demonstrate that even three trophic level interactions with only five interacting species are not predictably simple. The interpretation of the stable isotope results and consumed-excreted weights indicate that: a) behaviour and microscopic observations should not be ignored in competition-predation interactions, and b) functional guilds can take advantage of more diverse food opportunities. The reality of mixed diets complicates functional guild assignments that are reflected in 15N and 13C isotope levels at natural abundances in the environment. Microcosm experiments with this sensitive technique can help decipher the interpretation of rare isotope natural abundance values, as well as providing measured consumption, growth, and excretion rate values for modelling soil food web interactions.